Caffeine consumption and mortality in diabetes: An analysis of NHANES 1999-2010 - Neves, J (2018)
Aim: An inverse relationship between coffee consumption and mortality has been reported in the general population. However, the effect of coffee consumption in diabetes remains unclear. We aimed to evaluate the association of caffeine consumption and caffeine source with mortality among patients with diabetes. Methods: We examined the association of caffeine consumption with mortality among 1974 women and 1974 men with diabetes, using the National Health and Nutrition Examination Survey (NHANES) 1999-2010. Caffeine consumption was assessed at baseline using 24 h dietary recalls. Cox proportional hazard models were fitted to estimate hazard ratios (HR) for all-cause, cardiovascular, and cancer-related mortality according to caffeine consumption and its source, adjusting for potential confounders. Results: A dose-dependent inverse association between caffeine and all-cause mortality was observed in women with diabetes. Adjusted HR for death among women who consumed caffeine, as compared with non-consumers, were: 0.57 (95% CI, 0.40-0.82) for <100 mg of caffeine/day, 0.50 (95% CI, 0.32-0.78) for 100 to <200 mg of caffeine/day, and 0.39 (95% CI, 0.23-0.64) for =200 mg of caffeine/day (p = 0.005 for trend). This association was not observed in men. There was a significant interaction between sex and caffeine consumption (p = 0.015). No significant association between total caffeine consumption and cardiovascular or cancer mortality was observed. Women who consumed more caffeine from coffee had reduced risk of all-cause mortality (p = 0.004 for trend). Conclusion: Our study showed a dose-dependent protective effect of caffeine consumption on mortality among women with diabetes.